The role of alpha-fetoprotein in the tumor microenvironment of hepatocellular carcinoma - Lu, Yan; Lin, Bo; Li, Mengsen (Frontiers in Oncology, 2024)
Hepatocellular carcinoma (HCC) is a prevalent malignant cancer worldwide, characterized by high morbidity and mortality rates. Alpha-fetoprotein (AFP) is a glycoprotein synthesized by the liver and yolk sac during fetal development. The serum levels of AFP exhibit a significant correlation with the onset and progression of HCC. Extensive research has demonstrated that the tumor microenvironment (TME) plays a crucial role in the malignant transformation of HCC, and AFP is a key factor in the TME, promoting HCC development. The objective of this review was to analyze the existing knowledge regarding the role of AFP in the TME. Specifically, this review focused on the effect of AFP on various cells in the TME, tumor immune evasion, and clinical application of AFP in the diagnosis and treatment of HCC. These findings offer valuable insights into the clinical treatment of HCC.